Plant recovery from seedling-derived shoot tips of Faidherbia albida grown in vitro - Ruredzo, T.J.; Hanson, Jean (Springer, 1993)
In vitro cultures were initiated from shoots taken from seedlings of Faidherbia albida on Murashige and skoog based medium supplemented with different combinations of 6-benzylaminopurine (BA) and alpha-raphthaleneacetic acid (NAA). The shoots grew and rooted on all media. Rooting and vigorous growth were most successful on medium supplemented with 10-M NAA alone on which 87 percent of the shoots formed roots. Seventy-one percent of plantlets which were transfered to soil were successfuly established and nodulated with the native Rhizobium. The procedures provided a basis for the development of in vitro techniques for rapid multiplicaiton and physiological studies of the species.